Rite, flesh, and stone : the matter of death in contemporary Spanish culture - Cordoba, Antonio; García-Donoso, Daniel (Hispanic issues (Vanderbilt University), 2021)
"How death has been conceived of and represented in Spanish culture since the second half of the twentieth century"--